Perencanaan Kampanye “Vitiligo Between Us” Dalam Membangun Kesadaran Generasi Z Jakarta Akan Penyakit Vitiligo - Diffa Putri Andriyani; Siti Anisatul Barroh (Jurnal Pendidikan Indonesia, 2025)
Vitiligo is a skin disease that involves depigmentation of the skin resulting in white patches on the surface of the skin caused by an autoimmune reaction that attacks the skin's pigment cells. External factors that also cause vitiligo include stress, sun exposure, and certain chemicals. The lack of public understanding and awareness of vitiligo causes discrimination against vitiligans by society due to misperceptions and bad stigma. “Vitiligo Between Us” campaign planning consisted of social media campaign as pre-event, seminar as main event, short interview, Instagram video reels competition and recap of campaign activities as post event. The purpose of this work is to plan the "Vitiligo Between Us" campaign program to build public awareness, especially generation Z, about vitiligo. The campaign was designed using the Strategic Planning for Public Relations model by Ronald D. Smith which consists of 4 phases and 9 steps. This campaign planning is expected to build awareness of vitiligo disease among generation Z in Jakarta.